(untitled) (Journal of Enam Medical College, 2024)
Background: Street vended, ready to eat vegetable salads are consumed raw, often without heat treatment. Consequently, understanding their role in the spread of antibiotic resistant bacteria cannot be overemphasized. Objective: To study microbiological quality of street vended, vegetable salads sold in Minna metropolis in Nigeria. Materials and Methods: Fourteen (14) vegetable salads were sampled randomly in duplicates from street venders within Minna metropolis between June 2019 to November 2019. These samples were examined for the presence of bacterial isolates using standard cultural methods. Antibiotic susceptibility testing of the bacterial isolates was achieved by the disk diffusion technique. Results: Result analysis revealed 1.06 × 107 cfu/g mean total viable bacterial count. Similarly, the mean total coliform bacterial count was 0.94 × 107 cfu/g. The study revealed that all the sampled vegetable salads contained four or more bacteria. Staphylococcus aureus was the most frequent (19.5%), followed by Shigella and Klebsiella sp., (12.2%). However, E. coli, E. faecalis and Enterobacter sp. were less frequent (2.4%). The isolated Gramnegative bacteria exhibited resistance (≥ 73%) to amoxicillin/clavulanate, gentamicin, ofloxacin, cefuroxime and ampicillin. Furthermore, the isolated Gram-positive bacteria showed resistance to cefuroxime, ceftriaxone and amoxicillin/clavulanate in ≥ 40% cases. Multidrug resistant bacteria were 97.6% (40/41), of which 61.0% (25/41) was resistant to four or more antibiotics and have Multiple Antibiotic Resistance Index (MARI) ranging from 0.5 to 1.0. Conclusion: The results of this study show that street vended, ready to eat vegetable salad facilitates the transmission of clinically relevant antibiotic resistant bacteria. Therefore, appropriate measure should be enforced to ascertain the wholesomeness of street vended, ready to eat vegetable salad as the spread of the bacteria contaminant to humans by ingestion cannot be dismissed. J Enam Med Col 2021; 11(3): 164-172